Features of the implementation of the phenomenon "musicity" in dance tango - Zherobkina, Kateryna; Fomenko, Borys; Mukin, Vladyslav (Professional Art Education, 2024)
The article provides a holistic analysis of the features of the implementation of the phenomenon of «musicality» in choreographic art, in particular in Tango dance. Methods & methodology. The article used the principles of ambiguity, systematicity, historicism; methods of embodying musicality in dance through forms of perception, creation, performance (interpretation) and improvisation. The scientific novelty of the article is to determine the content of the methods of musicality in Tango dance, as a reflection of psychological, performing, expert and artistic aspects; to reveal the etymology of the word «tango»; to determine the stages of formation and development of Tango dance; to distinguish specific types (Creole, Argentine, Ballroom and Finnish) of tango; to substantiate the forms - stage, sports and social. Results. As a result of scientific research, it was found that Tango is a whole system of concepts, images, words and practices. It is impossible to understand a part of the whole if it is isolated from other parts of it. In the context of Tango, dance acquires meaning together with music, bandoneon – with the evoked nostalgia, memories from the past together with a certain way of visualizing the world, which is characteristic of true love for Tango. It is determined that Tango dance represents a musical and choreographic genre that integrated Afro-Argentine candombe and Andalusian tango, Argentine milonga, European polka and waltz, Spanish contradanza and Cuban habanera, the key feature of which is unpredictability. It is a progressive pair dance of a man and a woman, performed in a closed (contact or close) position, based on the principles of partner interaction, contrast and improvisation. Conclusions. Analysis of the multifaceted nature and multi-valued connotations of the phenomenon of «musicality» in choreographic art allows us to identify various methods of its embodiment in Tango dance, such as methods of developing and educating dancers’ musical abilities, methods of expert assessment of performing skills, and methods of artistic embodiment of musicality in dance forms.